ANALISIS PERSPEKTIF TIM KREATIF ATAS KONTEN PEMBERITAAN PEMBANGUNAN IBU KOTA NEGARA DI AKUN MEDIA SOSIAL INSRAGRAM MATA MILENIAL INDONESIA - Safira, Nur Kholifah (Synergy : Jurnal Ilmiah Multidisiplin, 2024)
This research is entitled " analysis of the creative team's perspective on news content on the development of the nation's capital on indonesian mata millenial instagram social media account". This research method uses qualitative research using data from 3 informants as a source of obtaining data. understanding of data analysis as "an effort to systematically search for and organize records of observations, interviews, and others to increase the researcher's understanding of the cases studied and present them as findings to others. The Creative Team is a group of people who in this position carry out several tasks such as generating creative ideas and conducting research to support material needs programs, programs creating scripts and holding meetings to discuss planning and development programs. The development of information technology brings a change in society. One result of technological developments is social media. The birth of social media makes people's behavior patterns experience a shift in culture, ethics and existing norms. 50 employees, based in the South Jakarta area. One of the content presented on the Indonesian Millennial Eye's Instagram social media is about the construction of a new National Capital City (IKN). In this regard, information from content presented on social media.